The Role of the Chief Strategy Officer - Angwin, Duncan; Powell, Taman (MIT Sloan Management Review, 2012)
The Chief Strategy Officer (CSO) is a comparatively new but increasingly important role in many organizations. To explore the role of the CSO, the authors conducted 24 interviews with CSOs at U.K. companies that are part of the FTSE 100 Index, across a number of industrial sectors. Secondary data - company reports, strategy documents and presentations - were used to complement the interviews. From this study of interviews and secondary data, the authors have developed a typology of four CSO archetypes - Internal Consultant, Specialist, Coach and Change Agent - who carry out a variety of responsibilities in the role of the CSO. By understanding how the duties of the CSO can vary significantly from organization to organization, boards and CEOs can make better decisions about which type of CSO is necessary for their leadership teams.